Estudio experimental de tráfico de video en redes IPv6 multicast IEEE 802.11ac - Facchini, Higinio Alberto (2019)
The growing number of multimedia users involves an exponential increase in bandwidth requirements on networks. Consumers are increasingly demanding in terms of quality and performance of products based on video. This paper proposes an experiment of multicast video traffic in a network of a real laboratory as test bed, with clients working in the IEEE 802.11ac standard, and using IPv6. The videos were encoded in H.264, H.265, VP8 and Theora. And the experiments were carried out using a trailer of the movie Star Trek, and alternately for contrast, a video of a videoconference using Adobe Connect, of the same duration. This work is a continuation of experience made on wired networks for video traffic. The conclusions of the work will help to determine the configurations to be taken into account for the adequate management of similar networks and efficient use of resources available, without compromising the performance and QoS expected.